Education and employment outcomes in clients of the Nurse–Family Partnership. Issue 2 (5th February 2020) - Flowers, Michael; Sainer, Shannon; Stoneburner, Ashley; Thorland, William
Abstract: Objectives: Nurse–Family Partnership (NFP) is an evidence‐based home visitation program designed for low‐income, first‐time mothers to support pregnancy, child development, and maternal self‐sufficiency. This study examined educational and employment outcomes among NFP clients compared to a reference sample. Design: Entropy balancing and a difference‐in‐difference design were used to compare the two samples of women from 2007 to 2016. Sample: There were 127, 427 women in the NFP sample, and 787 women in the reference cohort. Measurements: Educational outcomes included high school completion and employment outcomes consisted of employment status. Results: Across a one‐year interval, NFP mothers with less than a high school diploma or general education diploma (GED) at baseline showed a 9.5 percentage point increase in diploma or GED attainment compared to the reference mothers [95% CI: 0.015–0.180]. Similarly, mothers enrolled in NFP who were not employed at baseline showed a 7.8 percentage point increase in employment compared to the reference mothers [95% CI: 0.003–0.150]. Conclusions: The findings in this study show positive results for NFP mothers attaining high school completion and employment compared to mothers in the reference group. Such findings are of importance with regard to progression toward economic self‐sufficiency and corresponding reduction of health disparities.